2021
DOI: 10.3390/ijerph18189556
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and eHealth Literacy in the Era of COVID-19: A Cross-Sectional Study in a Peripheral Clinic in Israel

Abstract: The COVID-19 pandemic mandating isolation, quarantine, and social distancing has accelerated and expanded the use of telemedicine. This study examines the extent of the use of telemedicine and the relationship between eHealth literacy and satisfaction with using telemedicine during the pandemic. A total of 156 participants from a clinic in a peripheral community in southern Israel completed an online questionnaire. We found that 85% knew how to use the internet for health information, but only one third felt s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…A range of factors appeared to influence the acceptance of telehealth physiotherapy as an alternative option in selected participants. That it was considered to be a necessary adaption to ensure a continued service of delivery during the COVID-19 pandemic, when stay-at-home orders were stipulated, has been similarly reported in other populations [ 25 , 27 , 30 ]. The reduced burden of travel with telehealth services compared to in-person consultation has also been observed for those with chronic conditions [ 25 , 34 ], with lower reports of physical exhaustion in those with chronic respiratory conditions undertaking telehealth [ 30 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A range of factors appeared to influence the acceptance of telehealth physiotherapy as an alternative option in selected participants. That it was considered to be a necessary adaption to ensure a continued service of delivery during the COVID-19 pandemic, when stay-at-home orders were stipulated, has been similarly reported in other populations [ 25 , 27 , 30 ]. The reduced burden of travel with telehealth services compared to in-person consultation has also been observed for those with chronic conditions [ 25 , 34 ], with lower reports of physical exhaustion in those with chronic respiratory conditions undertaking telehealth [ 30 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 85%
“…That it was considered to be a necessary adaption to ensure a continued service of delivery during the COVID-19 pandemic, when stay-at-home orders were stipulated, has been similarly reported in other populations [ 25 , 27 , 30 ]. The reduced burden of travel with telehealth services compared to in-person consultation has also been observed for those with chronic conditions [ 25 , 34 ], with lower reports of physical exhaustion in those with chronic respiratory conditions undertaking telehealth [ 30 , 35 , 36 ]. Reducing the risk of viral transmission during a pandemic [ 37 ] or the risk of infection linked to attending a healthcare facility [ 30 ], a particular concern for those with bronchiectasis, was also a perceived benefit of engaging with telehealth.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The review concluded that telephone consultations were used more by younger working-age people, the very old, and non-immigrants, with internet-based consultations more likely to be used by younger people ( 26). An additional survey from Israel reported a positive association between younger age and higher eHealth literacy and satisfaction and usage of telemedicine (27).Efforts should be made to prevent inequalities in delivering primary care due to structural differences. Despite relatively high patient comfort to receive remote care, some prevalent di culties were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The use of telemedicine significantly increased during the COVID-19 pandemic, which during a lock down period is the only means of contacting, monitoring, and advising patients with chronic diseases or those in postoperative care [ 13 , 14 , 15 ]. The need of maintaining social distancing to reduce infection risks, while also avoiding deterioration to patients’ medical conditions and providing them with an adequate healthcare was the main reason to develop a standardized questionnaire, destined for patient undergoing pterional and other neurosurgical approaches, requiring an incision of the temporal muscle, for different cranial pathologies.…”
Section: Discussionmentioning
confidence: 99%